Road Incidents Emergency Service- A Case Study for Locating and Equipping Fire Brigades - Paliska, Dejan (Promet - Traffic&Transportation, 2003)
This paper presents the application of MLCP location-allocationmodel in GIS environment to optimise the number andlocations of fire brigade units, which would intervene in case ofroad incidents. There are 40 fire brigade units that are more orless equipped and trained to intervene in such cases. For simulationpurposes, a potential demand for intervention of emergencysquads was calculated, and the potential spatial accessibilitywas investigated.